PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMANDIRIAN DAN PRESTASI BELAJAR SISWA (Studi Pembelajaran IPS Kelas IV SDN 47 Bengkulu Selatan) - Amanda Riti Lestari; Turdjai Turdjai (DIADIK, 2020)
Thepurposeof thisstudytodescribe,(1)howtheapplicationofthemodelofproblembased learningcanimprovetheindependenceofstudents, (2)whether themodelofproblembased learningcanimprovestudentlearningachievement,and(3) theeffectivenessof theapplicationof problembased learning modelsin improvinglearningachievementlearners.Thisresearch isa combinationresearchusingclassroomactionresearchthencontinuedwithquasi-experimental. ThesubjectsoftheclassactionresearchwerestudentsofclassIVSDN47SouthBengkulu,while the  experimental  classclassIVASDN39SouthBengkuluandcontrolclassIVSDN39South Bengkulu.Datacollectionisdonebyobservationandlearningachievementtests.Dataanalysis usingratingschaleand different test.Theresults showedthat theapplicationoftheproblem based learningmodelcouldincreasetheindependence andlearningachievementofstudents,andthe applicationoftheproblembasedlearningmodelcouldeffectivelyimprove thelearning achievementofsocialstudies at SouthBengkulu